Correlation of Red Blood cell Parameters and glycemic control in Type 2 Diabetes Mellitus patients - وريده, هيا; روز سعيد ,; عطية خميس, (Latakia University Journal -Medical Sciences Series, 2023)
Background: Diabetes Mellitus Type 2 (T2DM) is a worldwide metabolic disorder characterized by persistent hyperglycemia and increased risk of microvascular and macrovascular complications that affect patients quality of life. The main concern of physicians is glycemic control. Consistent hyperglycemia causes functional and structural changes of red blood cells which may reflect on its parameters. Objective: Poor glycemic control is associated with high risk of developing diabetic microvascular complications. The main aim of this study is determining the RBCs parameters and their correlation to diabetic control, so we can evaluate the glycemic state and the risk of developing microvascular complications depending on these parameters. Methods: The study included 130 T2DM patients and 30 healthy control.HbA1, CRP, RBCs, Hct, Hb, MCV, MCH, MCHC and RDW were measured in these patients. The study was conducted from January 2021 to December 2021 in Tishreen University Hospital and Diabetic Center. Results: Red cell distribution width (RDW) was significantly higher in diabetic patients than in control subjects (P<0.001). It was also higher in patients with uncontrolled glycemia (HbA1c>7%) than those with good control (HbA1c ≤7%,P<0.001) Conclusion: RDW has recently been studied in many diseases. RDW is significantly higher in diabetic patients than healthy subjects and is particularly higher in uncontrolled glycemia and in patients with diabetic microvascular complications. KEY WORDS: Glycated Hemoglobin HbA1C ,Red blood cell Distribution Width RDW, C-Reactive Protein CRP ,Diabetes Mellitus.